2015
DOI: 10.1097/iae.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Caused by Pseudomonas Aeruginosa

Abstract: All isolates were susceptible to ceftazidime and levofloxacin, and all MIC 90s for isolates in the current period compared with isolates from 1987 to 2001 remained identical. Despite early and appropriate treatment, outcomes were generally poor with a high rate of enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
(37 reference statements)
1
15
0
3
Order By: Relevance
“…1 We thank them for contributing their experience with a recent outbreak of Pseudomonas aeroginosa in North India. 2 It would be of interest to know if the cause of the outbreak was discovered given prior experience with similar outbreaks related to contaminated ophthalmic solutions.…”
Section: Letter To the Editormentioning
confidence: 99%
“…1 We thank them for contributing their experience with a recent outbreak of Pseudomonas aeroginosa in North India. 2 It would be of interest to know if the cause of the outbreak was discovered given prior experience with similar outbreaks related to contaminated ophthalmic solutions.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Though just 4.1% of isolates in the EVS study were gram-negative organisms, other studies suggest a higher incidence that ranges from 10 to 24% [2][3][4][5][6][7][8]. Among gram-negative endophthalmitis cases, Pseudomonas aeruginosa is the most commonly isolated organism [3,[9][10][11][12] and is associated with a more fulminant clinical course and higher evisceration/enucleation rate compared to its gram-positive counterparts [13][14][15]. In fact, a recent prospective study by Stevenson et al reported 30% of patients with gram negative endophthalmitis requiring evisceration or enucleation [8].…”
Section: Introductionmentioning
confidence: 86%
“…O prognóstico também varia conforme o agente etiológico. Infecção por Staphylococcus coagulase-negativa, geralmente, é de melhor prognóstico (117,118) ; infecção por Staphylococcus aureus, Streptococcus e bactérias Gram-negativas, geralmente, são mais graves e com pior prognóstico (119)(120)(121) . Com as técnicas que permitem a identificação do agente etiológico em menos de 24 horas, estudos baseados nos diferentes agentes detectados devem ser revisados quanto à conduta e prognóstico.…”
Section: Prognóstico Visualunclassified
“…(150) . aquosos (120,151) . A identificação de tais agentes é de extrema importância para se controlar surtos de endoftalmites, com a fiscalização dos processos de esterilização e orientação de cuidados pós-operatórios.…”
Section: Aspectos Relacionados à Fonte De Infecçãounclassified
See 1 more Smart Citation